2021
DOI: 10.1096/fj.202100085r
|View full text |Cite
|
Sign up to set email alerts
|

Gasdermins mediate cellular release of mitochondrial DNA during pyroptosis and apoptosis

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 54 publications
(129 reference statements)
3
51
0
Order By: Relevance
“…Pyroptosis and intrinsic apoptosis are two forms of regulated cell death driven by active caspases. Caspase-1 induces GSDMD pore formation during pyroptosis, whereas caspase-3 promotes GSDME pore formation during apoptosis [ 31 ]. Our results showed that TNF-α activated caspase-3, and further induced GSDME-mediated pyroptosis in HUVECs.…”
Section: Discussionmentioning
confidence: 99%
“…Pyroptosis and intrinsic apoptosis are two forms of regulated cell death driven by active caspases. Caspase-1 induces GSDMD pore formation during pyroptosis, whereas caspase-3 promotes GSDME pore formation during apoptosis [ 31 ]. Our results showed that TNF-α activated caspase-3, and further induced GSDME-mediated pyroptosis in HUVECs.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of cancer cells or normal cells, GSDME-mediated pyroptosis is closely associated with mitochondrial apoptosis. The pore-forming activity of GSDME-N extends beyond the cell membrane to the mitochondrial membrane, which permeabilizes mitochondria to release cytochrome C and mtDNA ( Rogers et al, 2019 ; de Torre-Minguela et al, 2021 ). The crosstalk between GDSME and GSDMD, which are the crucial proteins in the gasdermin family mediating pyroptosis, deserves attention.…”
Section: Discussionmentioning
confidence: 99%
“…Another research further indicated that GSDME-N permeates mitochondria preferentially, and ruptures the plasma membrane later ( Rogers and Alnemri, 2019 ). Mitochondrial DNA (mtDNA), as a DAMP, is released out of the mitochondria in the pore formation constructed by GSDME-N, and removed extracellularly upon rupture of the plasma membrane ( de Torre-Minguela et al, 2021 ). Additionally, GSDME-N also induces mitochondrial network fragmentation during pyroptosis and apoptosis ( de Torre-Minguela et al, 2021 ).…”
Section: Gsdme-mediated Programmed Cell Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this was a useful distinction, the historic application of the term “apoptosis” to target cell death upon CTL attack does not imply that it meets the stringent molecular criteria for apoptosis as it is defined today, nor that other related RCD modalities have been excluded. Many classical morphological and molecular features of apoptosis such as membrane blebbing, caspase-3/6/8/9 activation, PARP cleavage, PS exposure, mitochondrial permeabilization, and DNA fragmentation can be shared with other RCD modalities, and thus conventional apoptosis assays such as AnnexinV and TUNEL staining are not specific for apoptosis ( 98 104 ). That is not to say, however, that apoptosis is not an important mechanism of cell death upon CTL attack; in all likelihood, the mechanism of target cell death may be context-dependent, and subject to change based upon the characteristics of both the CTL and target cell populations.…”
Section: Choreography Of the Target Cell Response To Ctl Attackmentioning
confidence: 99%